Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

My math problem is a bit more tricky than it sounds in the caption. I have the following Task (which i in fact do not understand):

"Determine the Fourier series for $f(x)=\lvert \sin{x}\rvert$ in order to build the Sum for the series: $\frac{1}{1*3}+\frac{1}{3*5}+\frac{1}{5*7}+\dots$"

My approach: first, calculating the Fourier series. There is no period, Intervall or Point given. i think it must turn out to be something like this: $a_{n} = \frac{2}{\pi} \int_{0}^{\pi} |\sin x|\cos nx dx$ but what would be the next step to build the series?

and second: the other given series. I think its all about the uneven numbers, so i have in mind 2n-1 and 2n+1 are the two possible definitions. So it could be something like this:

$(\frac{1}{1\cdot 3}+\frac{1}{3\cdot 5}+\frac{1}{5\cdot 7}+\dots) = \sum\limits_{n=1}^{\infty} \frac{1}{(2n-1)(2n+1)}$

But i cannot make the connection between this series, its sum and |sin x|.

despite i think the sum should be something around $\sum\limits_{n=1}^{\infty} \frac{1}{(2n-1)(2n+1)} = \frac{1}{2}$ (but i cannot proof yet)

please help me!

P.S.: i know the other Convergence of Fourier series for $|\sin{x}|$ -question here at stackexchange, but i think it doesn't fit into my problem. despite i don't understand their Explanation and there is no way shown, how to determine the solution by self.

P.P.S: edits were made only to improve Latex and/or language

share|improve this question

1 Answer 1

up vote 2 down vote accepted

You were on the right track. First, calculate the Fourier series of $f(x)$ (you can leave out the magnitude signs because $\sin x \ge 0$ for $0\le x \le \pi$ ): $$a_n=\frac{2}{\pi}\int_{0}^{\pi}\sin x\cos nx\;dx= \left\{ \begin{array}{l}-\frac{4}{\pi}\frac{1}{(n+1)(n-1)},\quad n \text{ even}\\ 0,\quad n \text{ odd} \end{array}\right .$$ For $a_0$ we get $a_0=\frac{2}{\pi}$. Therefore, the Fourier series is $$f(x) = \frac{2}{\pi}-\frac{4}{\pi}\sum_{n \text{ even}}^{\infty}\frac{1}{(n+1)(n-1)}\cos nx=\\ =\frac{2}{\pi}\left ( 1-2\sum_{n=1}^{\infty}\frac{1}{(2n+1)(2n-1)}\cos 2nx \right )\tag{1}$$

Now we can evaluate the series. Set $x=\pi$, then we have $f(\pi)=0$ and $\cos 2n\pi = 1$. Evaluating (1) with $x=\pi$ we get $$0 = 1 - 2\sum_{n=1}^{\infty}\frac{1}{(2n+1)(2n-1)}$$ which gives your desired result.

share|improve this answer
1  
You might note that $f$ is Lipschitz at $x=\pi$ so that the series converges to $f(\pi)$. –  copper.hat May 10 '13 at 19:18
    
oh yeah, thanks, you saved my day. but i think i will still need some time to think over this solution. –  Toralf Westström May 10 '13 at 19:24

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.